2004
DOI: 10.1016/j.ydbio.2003.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of Notch signaling genes in the embryonic pituitary: Prop1 deficiency affects Notch2 expression

Abstract: Normal development of the pituitary gland requires coordination between the maintenance of a progenitor cell pool and the selection of progenitor cells for differentiation. As Notch signaling controls progenitor cell differentiation in many embryonic tissues, we investigated the involvement of this important developmental pathway in the embryonic pituitary. We report that expression of Notch signaling genes is spatially and temporally regulated in pituitary embryogenesis and implicate Notch2 in the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 57 publications
3
118
0
Order By: Relevance
“…While Dll3 is not expressed in early stages of Rathke's pouch formation, its expression is detectable at E14.5 and E17.5 in the intermediate lobe as reported previously (Supplementary Fig. 1), although no defect in melanotrope differentiation was observed in Dll3 −/− embryos (Raetzman et al 2004).…”
Section: Core Components Of the Notch Signaling Pathway During Pituitsupporting
confidence: 84%
See 1 more Smart Citation
“…While Dll3 is not expressed in early stages of Rathke's pouch formation, its expression is detectable at E14.5 and E17.5 in the intermediate lobe as reported previously (Supplementary Fig. 1), although no defect in melanotrope differentiation was observed in Dll3 −/− embryos (Raetzman et al 2004).…”
Section: Core Components Of the Notch Signaling Pathway During Pituitsupporting
confidence: 84%
“…Therefore, identifying the critical factors initiating Prop1 gene expression will provide further insights into the integration of the Notch pathway with other developmental programs. It has been reported recently that Prop1 is required for Notch2 protein expression in the pituitary (Raetzman et al 2004). However, our in situ hybridization analyses of Prop1 −/− embryos showed that expression of Notch2 and Hes1, which is dependent on Notch signaling, is not significantly affected (Raetzman et al 2004; our unpublished data), suggesting that deletion of Prop1 is not sufficient to downregulate Notch signaling during pituitary development.…”
Section: Notch Activation Controls Formation Of Pit1 Precursorsmentioning
confidence: 99%
“…In mouse, Pit1 expression requires the concerted action of Wnt/-catenin signaling and the paired-like homeodomain transcription factor Prop1, which also affects the Notch pathway (Raetzman et al, 2004, Olson et al, 2006, Zhu et al, 2007. However, also here, it is not understood how these pathways might contribute to Pit1's spatial restriction, while in zebrafish, neither Prop1 nor canonical Wnt genes have been described in the context of AH development at all.…”
mentioning
confidence: 87%
“…In general, there is no co-localization of PROP1 or SOX2 with hormones (Chen et al 2009;Fauquier et al 2008;Fu et al 2012a,b;Garcia-Lavandeira et al 2009;Gremeaux et al 2012;Yoshida et al 2009), supporting the general notion that stem cell conservators must be downregulated before differentiation starts. The NOTCH pathway is another essential regulator of pituitary embryogenesis (Kita et al 2007;Monahan et al 2009;Raetzman et al 2004;Zhu et al 2005Zhu et al , 2007, of which several components are upregulated in the adult (mouse) pituitary stem cell fraction (Chen et al 2006(Chen et al , 2009Vankelecom 2010) and are found expressed in some of the MZ and parenchymal S100 þ cells of the (rat) AP (Tando et al 2013). Some other transcriptional regulators that play an important role in pituitary embryonic development (such as Hesx1, the earliest known gene expressed in the pituitary primordium, Lhx4, Pax6, Otx2, Ascl1 and the Six/Eya/ Dach genes; Kelberman et al 2009;Zhu et al 2005Zhu et al , 2007 are also higher transcribed in the adult pituitary stem cell fraction (Chen et al 2006(Chen et al , 2009reviewed in Vankelecom 2010reviewed in Vankelecom , 2012, as well as the cyclin-dependent kinase inhibitor p57 that, during embryogenesis, emerges in the RP progenitor cells that stop cycling to embark on differentiation (Bilodeau et al, 2009;Vankelecom 2010;Vankelecom and Chen 2014).…”
Section: Pituitary Stem Cells: Expanding Molecular Portrayalmentioning
confidence: 99%
“…Genetic disruptions of SOX2 leads to certain forms of hormonal cell deficiency and pituitary hypoplasia (Jayakody et al 2012;Kelberman et al 2008), at least partly due to a reduced expansion and function of the RP progenitor cells, thereby giving some hint toward the importance of SOX2 in adult stem cell regulation. NOTCH signaling is likely also involved in the control of stem cell proliferation in the adult gland, since NOTCH downregulation in the embryonic pituitary coincides with cell cycle exit of the RP progenitor cells and genetic ablation of NOTCH signaling in the developing pituitary results in severe AP hypoplasia due to reduced proliferative capacity of RP progenitors (Kita et al 2007;Monahan et al 2009;Raetzman et al 2004;Tando et al 2013;Zhu et al 2005Zhu et al , 2007. In addition, stem cells increase in number in AP cell cultures upon NOTCH activation (Chen et al 2006;Tando et al 2013).…”
Section: Pituitary Stem Cells: Expanding Molecular Portrayalmentioning
confidence: 99%